Numerical analysis of scattering a pulsed signal from antennas and radar objects - P. V. Sukhacheuski (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The results of a numerical study of the envelopes of radio pulses scattered from wire antennas, a cylinder, a rocket of class air-to-ground are given. The spectral method and the method of moments are used.